Long contraction scour - Koh, Chun Wei (Nanyang Technological University, 2020)
The most common cause of bridge structure damage in the world today is due to a natural phenomenon called “scouring”. Contraction scour is usually the main concern when it comes to constructing hydraulic structure such as bridges, barrages, cross drainage and weirs. Scour holes are formed at the structure abutment due to the erosive action of flowing water through the river channel that has resulted in the removal of sediments on erodible beds. These scour holes will affect the structure stability and its lateral bearing capacity, which eventually leads to the collapse of the bridge. Therefore, it is important to understand this phenomenon in order to maintain the durability and life of hydraulic structure. Hence, the objective of this study is to study the phenomenon of long and gradual contraction scouring in an open channel flow. Results obtained from experiments by past researchers were utilised to carry out a dimensional analysis on the relevant variables that affect the size and depth of scouring. Using the incomplete self-similarity method and regression analysis of the database, a predictive scour depth equation was proposed which is suitable for applications with uniform and non-uniform sediments. It was found that the maximum scour depth in a long contraction depends mainly on the effect of the densimetric Froude number (Fo,d84), width ratio of the uncontracted to the contracted channel (B1/B2), sediment gradation (σg), and the relative sediment size (d84/h1). From the proposed equation 4.5, it able to correlate all the 206 data of uniform and non-uniform sediments and fall within ± 30% range with R2 value of 0.8.